2011
DOI: 10.1182/blood-2010-07-295113
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic combinatorial interactions of RUNX1 and cooperating partners regulates megakaryocytic differentiation in cell line models

Abstract: Specific interactions of transcription factors (TFs) with their targets are crucial for specifying gene expression programs during cell differentiation. How specificity is maintained despite limited selectivity of individual TF-DNA interactions is not fully understood. RUNX1 TF is among the most frequently mutated genes in human leukemia and an important regulator of megakaryopoiesis. We used megakaryocytic cell lines to characterize the network of RUNX1 targets and cooperating TFs in differentiating megakaryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
89
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(98 citation statements)
references
References 47 publications
(68 reference statements)
8
89
1
Order By: Relevance
“…We then conducted a bioinformatics-based screen using microarray data on CREB overexpression and CREB chromatin immunoprecipitation-sequencing (ChIP-Seq) data using data available at Encyclopedia of DNA Elements (ENCODE) and elsewhere to identify regulators of CREB function in hematopoietic cells (Esparza et al, 2008;Jolma et al, 2010;Pencovich et al, 2011;Raney et al, 2011;Trompouki et al, 2011;Martens et al, 2012). Using insight gained from bioinformatics, we discover that the bone morphogenetic protein (BMP) signaling pathway acts downstream of PKA-CREB signaling in regulating AGM hematopoiesis.…”
Section: Genomic Binding and Interaction Of Creb In K562 Cellsmentioning
confidence: 99%
“…We then conducted a bioinformatics-based screen using microarray data on CREB overexpression and CREB chromatin immunoprecipitation-sequencing (ChIP-Seq) data using data available at Encyclopedia of DNA Elements (ENCODE) and elsewhere to identify regulators of CREB function in hematopoietic cells (Esparza et al, 2008;Jolma et al, 2010;Pencovich et al, 2011;Raney et al, 2011;Trompouki et al, 2011;Martens et al, 2012). Using insight gained from bioinformatics, we discover that the bone morphogenetic protein (BMP) signaling pathway acts downstream of PKA-CREB signaling in regulating AGM hematopoiesis.…”
Section: Genomic Binding and Interaction Of Creb In K562 Cellsmentioning
confidence: 99%
“…6D). Members of these three families of TFs were previously shown to collaborate with RUNX TFs (20,23) and to serve essential functions in NKC (51)(52)(53). ChIP-seq of T-bet was performed in Th1 cells (54) in which Runx3 expression is induced in a T-bet-dependent manner (55).…”
Section: Il-15 Alone (41) Administration Of Il-15/r␣ To Wt or Runx3mentioning
confidence: 99%
“…ChIP was performed essentially as described previously (20). Briefly, cross-linked chromatin from approximately 40 ϫ 10 6 NKC (duplicate, each from three mice) was prepared and fragmented to an average size of ϳ200 bp by 40 cycles of sonication (30 s of sonication and 30 s of rest each) in 15-ml tubes using the Bioruptor UCD-200 sonicator (Diagenode, Liege, Belgium).…”
Section: Mice Generation Of Runx3mentioning
confidence: 99%
See 1 more Smart Citation
“…In the CMK line, looking at genes more specifically expressed in the later stages of MK differentiation (such as RAB27B), the authors showed enrichment for the ETS binding motif. They therefore proposed a model whereby RUNX1 controls early MK differentiation genes in collaboration with GATA1, whilst for genes which are more typically expressed in later stages, RUNX1 regulation is effected in collaboration with FOS/ JUN family members and ETS TFs [106]. Another example of how RUNX1 can regulate the expression of the same gene, but with different partners, is exemplified by the analysis of the promoter for myeloproliferative leukaemia (MPL, virus oncogene, the TPO receptor) where RUNX1 interacts with the SIN3A corepressor complex in haematopoietic stem and progenitor cells, whilst it forms a complex with the transcription activator EP300 (E1A-binding protein p300) on the same promoter in MKs [107].…”
Section: Runx1 In Partnershipmentioning
confidence: 99%